Uphill Capital Flows and the International Monetary System - Csonto, Balazs; Tovar Mora, Camilo (Washington, D.C. : International Monetary Fund, 2017)
Uphill capital flows constitute a key transmission channel through which reserve accumulation can distort the stability of the international monetary system. This paper examines and quantifies the importance of this transmission channel by examining how foreign official purchases of U.S. Treasuries influences the U.S. yield curve at different maturities. Our findings suggest that a percentage point increase in foreign official holdings relative to outstanding marketable securities reduces the term premium by 2.0-2.4 basis points at maturities of 2-3 years. These estimates are then used to gauge the role of a global policy in reducing excess reserve accumulation?e.g., a composite global reserve asset or through global liquidity facilities. Findings show that a policy that reduces the demand for Treasuries by USD 100 billion would increase yields by 1.5-1.8 basis points.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet